Prospective pedagogy for teaching chemical bonding for smart and sustainable learning - Dhindsa, H.; Treagust, David (R S C Publications, 2014)
As an important subject in the curriculum, many students find chemistry concepts difficult to learn and understand. Chemical bonding especially is important in understanding the compositions of chemical compounds and related concepts and research has shown that students struggle with this concept. In this theoretical paper based on analysis of relevant science education research, textbooks, and our classroom observations and teaching experiences, the authors argue that the difficulty in learning chemical bonding concepts is associated with the sequence (ionic, covalent and polar covalent bonding) in which students are taught because this sequence receives little support from constructivist theories of learning. Consequently, the paper proposes a sequence to teach chemical bonding (covalent, polar covalent and ionic bonding) for effective and sustainable learning. In this sequence, the concepts are developed with minimum reorganisation of previously learned information, using a format which is claimed to be easy for students to learn. For teaching these concepts, the use of electronegativity and the overlap of atomic orbitals for all types of bonding have also been stressed. The proposed sequence and emphasis on electronegativity and atomic orbital overlap meets the criteria for teaching and learning of concepts based on the psychology of learning including the theory of constructivism necessitating the construction of new knowledge using related prior knowledge. It also provides a better linkage between the bonding concepts learned at secondary and tertiary levels. Considering these proposed advantages for teaching, this sequence is recommended for further research into effective and sustainable teaching.